The Problem of Alienation and the Nietzsche’s Attempt to Overcome This in the Antichrist (Hermeneutical Reading of the First Chapter of the Antichrist) - Jalilzada, Khayyam (Scholarya Demo Journal of Ruby, 2020)
The main idol that Nietzsche wanted to break was Christianity. According to him, Christianity says no to life and body turning a man into a slave. Nietzsche calls the state of enslavement either to himself or to someone else an alienation. Accordingly, the main factor that alienates the (Western) people from themselves, others and from nature is Christianity. Socrates and Plato could not escape the criticisms of Nietzsche, who combated everything that harbored by Christianity. According to him, both names are among those who are nurtured by Christianity. However, Christianity, which he considered the cornerstone of Western civilization, was a greater danger for him than Socrates and Plato. The iconaclast philosopher emphasizes that Christianity makes man a slave to the Church and offers a philosophical method for war against Christianity. What is this philosophical method? “It is philosophy with a hammer”. Everything glorified by the society, the crowd is an idol according to Nietzsche. And when approaching these “idols”, we must always have the “hammer” in our hands. Here the “hammer” is the symbol of philosophical thinking. “Hammer” is the name of thinking with emotions by saying yes to body and life. As we approach the idol, we have to hit the idol with a hammer. Idols that are not solid and lack foundation will express their rottenness when we blow with the hammer. Nietzsche uses this philosophical method in each of his books against different idols, but in his work titled Antichrist, the idol hit by the hammer is clearly Christianity. In our article, we referenced Nietzsche’s work named Antichrist. We especially focused on the first part of the work in question, in which the criticisms of Christianity are heavily involved. Since our study was an attempt to apply the hermeneutical method, we tried not to go beyond the point where “the hammer was hit”. And in this way we tried to show how the hermeneutical method works. Therefore, the aim of our study is not to encompass Nietzsche’s philosophy, nor to address Nietzsche’s critique of Christianity in all its dimensions.